Prey preference of the stone crab Platyxanthus crenulatus (Decapoda: Platyxanthidae) in laboratory conditions - Laitano, Marìa Victoria (2013)
The preference for a particular type of prey implies an active behavioral choice of the predator. The present work deals with the prey preference of the large stone crab Platyxanthus crenulatus among similar sized gastropods and bivalves of different substrates using a recent proposed methodology based on a two-stage approach. In laboratory, crabs received different mollusk species separately to determine the consumption in number of each species when choice was not possible. Further, crabs were offered the same mollusc species but together to record differences of specific consumption when choice was possible. Results were then compared to assess prey preferences. Platyxanthus crenulatus is able to effectively attack and consume the majority of the sympatric mollusk species, although preferred the dominant species Brachidontes rodriguezii over the others. Such preference seems to be driven by shell shape and thickness which may be a common pattern in prey preference among large stone crab species.